Euler Totient Function Equations (Problem 2 2 )

ϕ ( x ) = ϕ ( x + 3 ) = ϕ ( 2 x ) = ϕ ( 2 x 2 ) = 4 \phi(x) = \phi(x + 3) = \phi(2x) = \phi(2x - 2) = 4

Find x x satisfying the equation above.

Notation: ϕ ( ) \phi(\cdot) denotes the Euler's totient function .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Possible solutions for ϕ ( x k ) = 4 \phi(x_k) = 4 are as follows:

x 1 × 1 2 = 4 x 1 = 8 x 2 × 4 5 = 4 x 2 = 5 x 3 × 1 2 × 4 5 = 4 x 3 = 10 \begin{array} {ll} x_1 \times \dfrac 12 = 4 & \implies x_1 = 8 \\ x_2 \times \dfrac 45 = 4 & \implies x_2 = 5 \\ x_3 \times \dfrac 12 \times \dfrac 45 = 4 & \implies x_3 = 10 \end{array}

Therefore x = x 2 = 5 x=x_2 = \boxed 5 , x 1 = 8 = x + 3 x_1 = 8 = x+3 , x 3 = 10 = 2 x x_3 = 10 = 2x , and 2 x 2 = 8 = x 1 2x-2 = 8 = x_1 .

Great solution!

Yajat Shamji - 10 months, 1 week ago

Log in to reply

Glad that you like it again.

Chew-Seong Cheong - 10 months, 1 week ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...